2010
DOI: 10.2176/nmc.50.1015
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid Hemorrhage Caused by a Ruptured Anterior Spinal Artery Aneurysm -Case Report-

Abstract: A 51-year-old man presented with an extremely rare case of intracranial subarachnoid hemorrhage caused by rupture of an anterior spinal artery aneurysm manifesting as disturbance of consciousness following sudden onset of neck pain and numbness of the extremities. Cranial computed tomography revealed subarachnoid hemorrhage, mainly in the posterior fossa. Cerebral angiography studies on admission and on the 4th day demonstrated no definite abnormality as a bleeding source. A ventricular catheter was inserted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…The pathogenesis of spinal artery aneurysms has been discussed. 10,18) Spinal artery aneurysms without inflammatory reaction, infection, or connective tissue disease have also been reported, as in the present case. Most spinal artery aneurysms are small with diameters of º3 mm, and although both saccular and fusiform aneurysms have been identified, the latter are more frequent.…”
Section: Case Reportsupporting
confidence: 76%
See 1 more Smart Citation
“…The pathogenesis of spinal artery aneurysms has been discussed. 10,18) Spinal artery aneurysms without inflammatory reaction, infection, or connective tissue disease have also been reported, as in the present case. Most spinal artery aneurysms are small with diameters of º3 mm, and although both saccular and fusiform aneurysms have been identified, the latter are more frequent.…”
Section: Case Reportsupporting
confidence: 76%
“…Most spinal artery aneurysms are small with diameters of º3 mm, and although both saccular and fusiform aneurysms have been identified, the latter are more frequent. 1,3,5,10,12,14,16,18,20,21) Three cases of spinal artery aneurysms were found to be fusiform dissecting lesions at surgery. 15) Some spinal artery aneurysms appear to be dissecting lesions.…”
Section: Case Reportmentioning
confidence: 99%
“…Ikeda et al presented a case of a ruptured PSA aneurysm that underwent spontaneous thrombosis confirmed intraoperatively with ICG video angiography and confirmed by histological examination which revealed organized thrombus formation within the aneurysm 3. Karakama et al reported a case of a ruptured ASA aneurysm causing subarachnoid hemorrhage that was managed conservatively with confirmed angiographic occlusion on follow-up 4. Pahl et al reported the spontenous resolution of a ruptured isolated cervical ASA aneurysm 7.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review reported only 26 cases of ruptured isolated spinal artery aneurysms in the literature. 15 Seven of those 26 aneurysms were located on the ASA, 5 on the artery of Adamkiewicz, 4 on the PSA, and the remaining aneurysms were fed by segmental or radiculomedullary branches.…”
Section: Discussionmentioning
confidence: 99%